1990
DOI: 10.1007/bf00318273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2 enrichment, nutrient addition, and fungal endophyte-infection on the growth of two grasses

Abstract: Increasing atmospheric carbon dioxide (CO) concentration is expected to increase plant productivity and alter plant/plant interactions, but little is known about its effects on symbiotic interactions with microorganisms. Interactions between perennial ryegrass, Lolium perenne (a C3 plant), and purpletop grass, Tridens flavus (a C4 plant), and their clavicipitaceous fungal endophytes (Acremonium lolii and Balansia epichloe, respectively) were investigated by growing the grasses under 350 and 650 μl l 1 CO at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 48 publications
3
48
2
Order By: Relevance
“…According to Wennström (1996) who studied E. typhina in the natural populations of Calamagrostis purpurea in Sweden, infected plants occurred only in wet habitats where nutrient levels were high, whereas in dry and nutrient poor habitats the fungus was absent. Other authors have shown that carbon dioxide enhanced the production of fungal stromata in infected plants but simultaneously in- hibited production of inflorescence in uninfected plants (Marks and Clay 1990;Groppe et al 1999;Meijer and Leuchtmann 2000). It has been reported that the small-scale habitat fragmentation can increase the intensity of infections with Epichloë in populations of Bromus erectus (Groppe et al 2001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Wennström (1996) who studied E. typhina in the natural populations of Calamagrostis purpurea in Sweden, infected plants occurred only in wet habitats where nutrient levels were high, whereas in dry and nutrient poor habitats the fungus was absent. Other authors have shown that carbon dioxide enhanced the production of fungal stromata in infected plants but simultaneously in- hibited production of inflorescence in uninfected plants (Marks and Clay 1990;Groppe et al 1999;Meijer and Leuchtmann 2000). It has been reported that the small-scale habitat fragmentation can increase the intensity of infections with Epichloë in populations of Bromus erectus (Groppe et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Such authors as Marks and Clay 1990, Wennström 1996, Groppe et al 1999, Meijer and Leuchtmann 2000, Groppe et al 2001, on the basis of experimental study indicate the importance of different environmental factors. It has been suggested that infection of host plants with E. typhina is a result of many factors.…”
Section: Introductionmentioning
confidence: 99%
“…Plants infected with fungal endophytes often grow faster than uninfected plants, although resource level can interact with infection in determining growth (Latch ei a/., 1985;Clay, 1987;Cheplick ei a/., 1989;Marks & Clay, 1990;Bacon, 1993;S.Marks, unpublished). Although many hypotheses have been advanced, the physiological basis of altered host plant growth remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These alkaloids also reduce insect herbivory on infected plants (Clay, 1988;Funk, White & Breen, 1993). Infected tall fescue plants exhibit enhanced growth, even in the absence of herbivory (Latch, Hunt & Musgrave, 1985;Clay, 1987;Cheplick, Clay & Marks, 1989;De Battista et al, 1990a;Marks & Clay, 1990) and are better competitors (Marks et al, 1991). Whilst these and many other studies have examined the effects of fungal-endophyte infection on whole plant responses, herbivory, and competition (Clay, 1988(Clay, , 1990, only two studies have examined the photosynthetic response (measured as carbon exchange rate) of grasses to endophyteinfection (Belesky et al, 1987;Richardson, Bacon & Hoveland, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of the mutualistic association between plants and endophytes have been thought to include improved growth of the infected plant ; however, the physiological basis of this effect is poorly understood, particularly for crop plants (Latch et al, 1985 ;Clay, 1987 ;Cheplick et al, 1989 ;Marks & Clay, 1990, 1996Bacon, 1993). Unlike previous experiments, where endophyte-free plants were obtained by treating infected plants with fungicide to eradicate the fungi, our approach was to obtain endophyte-free plants by using tissue culture for banana and by germinating sterilized seeds of maize in MS medium.…”
Section: mentioning
confidence: 99%